An Integrative Dual-Layer Poly-L-Lactic Acid Fibrous Membrane Prevents Peritendinous Adhesions - Wang, Wei; He, Ning; Yao, Zhixiao; Wang, Xu; Wang, Hui; He, Miao; Li, Yusheng; Qian, Yun (Frontiers in Bioengineering and Biotechnology, 2020)
Anti-adhesion membranes are prospective scaffolds for preventing peritendinous adhesion after injury. However, currently available scaffolds have some limitations, such as low efficacy for anti-adhesion, low quality of tendon healing, and unknown drug interactions. Thus, in this study, we designed an innovative structure involving an integrated dual-layer poly(L-lactic acid) (PLLA) electrospun membrane for preventing peritendonous adhesion by promoting tendon gliding. We investigated the surface morphology and wettability of the fiber scaffold. The adhesion and proliferation of fibroblasts were low on the PLLA fibrous membrane. Compared with single-layer membranes, the dual-layer PLLA fiber scaffold reduced adhesion to the tissues. The gliding space persisted until recovery in chicken extensor flexor tendons in vivo. Thus, this innovative PLLA membrane scaffold could prevent adhesion and promote gliding to facilitate tendon healing.